Reflections on the youth policy formulation: opportunities for the northern province of sri lanka - Jeevasuthan, S. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
The Northern Provincial Council (NPC) has realized the necessity to formulate a policy for its youth since its inception. Though several attempts were made to uplift the lives of the youth and to encourage and expedite the social development process based on the realization of the need for a youth policy, the NPC has realized that the absence of an inclusive and comprehensive youth policy. Such policy needs to addresses the challenges, the rights and responsibilities of the youth to implement suitable projects based on the social, economic and cultural contexts of all the severely war affected youth of the Province by sharing the available resources to the optimum level. It would be a herculean task to streamline the youth into social, economic, cultural and political mainstreams without formulating a youth policy. In the present context of the NP, legal challenges regarding the high-unemployment rate, frustration, non-participation in the socio-political activities, violence, alcohol and drugs abuse, and the resultant fear and abhorrence proliferated among the people. These threats that would impede the all domains of development of the whole province are perceptible now. Further, it is presumed that any youth development program or process implemented is neither producing the intended outcomes nor causing the desired effects. Considering this context, Ministry of Education, Cultural Affairs and Youth Affairs (NP) initiated the process of formulating a Youth Policy with the support from the United Nations Population Fund (UNFPA) in the year 2016. This study investigates into the formulation and the potential challenges insuch policy. A qualitative approach was employed with various stakeholders working with youth communities in different capacities. Recommendations were made in the draft policy in consideration with the international and national policies, accommodating the unique nature of the social, cultural, economic, and political fabric of the Northern Province.
Keywords: Northern Province; Youth policy; Policy Formulation & opportunities